Pemungutan Pajak Pertambahan Nilai dan Pajak Penghasilan Terhadap Pelaku Usaha Mikro dalam Pelaksanaan E-purchasing Pada Pengadaan Barang/Jasa Pemerintah - Antari, Vieka Ariestyani (Journal Evidence Of Law, 2024)
The government in order to regulate national development financing obtained from taxes, one of which is from the business sector, has published several regulations including the Regulation of the Minister of Finance of the Republic Indonesia Number 58/PMK.03/2022 concerning Appointment of Other Parties as Tax Collectors and Procedures for Collection, Deposit and/or Reporting Taxes Collected by Other Parties on Goods Procurement Transactions and/or Services Through the Government Procurement Information System. In order to development of MSMEs in the world of E-commerce, the Government also provides government goods/services procurement platform facilities that can be accessed by MSME business people to take part in providing goods/services using this method Epurchasing or purchasing electronically.